Pembelajaran PBL Kolaborasi PjBL untuk Meningkatkan Keterampilan 4C pada Mata Kuliah Pragmatik - Agus Darmuki; Ahmad Hariyadi; Nur Alfin Hidayati (Universitas PGRI Semarang, 2022)
This research was motivated by the low 4C skills in pragmatics courses for PBSI FKIP UMK students. The purpose of this study was to describe the improvement of 4C skills using the PjBL collaboration PBL model in pragmatics courses for students of the PBSI FKIP UMK Study Program. This research is a type of classroom action research through 2 cycles. Each cycle consists of planning, implementation, observation, and reflection. The object of this research is 30 students of PBSI FKIP UMK. Data collection techniques using observation, documentation, and tests. The data analysis technique used data triangulation. The results showed that there was an increase in the previous 4C skills from pre-cycle for knowledge construction skills 45% to 72% in cycle 1 and 80% in cycle 2, critical 46% in pre-cycle to 74 in cycle 1 and 82% in cycle 2, creativity 49% in pre-cycle to 75 in cycle 1 and 80% in cycle 2, and collaborative 54% to 75% and 80% in cycle 2. The conclusion shows an increase in 4C skills using the PjBL collaboration PBL model in the Pragmatics course in the PBSI FKIP UMK Study Program Academic Year 2021/2022.